Untethered : a novel - Jackson-Brown, Angela, 1968- (Harper Muse, 2024)
In the small college town of Troy, Alabama, amidst the backdrop of 1967, Katia Daniels lives a life steeped in responsibility. At the Pike County Group Home for Negro Boys, she pours her heart into nurturing the young lives under her care, harboring a longing for children of her own. Katia's romantic entanglement with an older man brings comfort but also stirs questions about the path she's chosen. The weight of her family's history bears down on her; a twin brother is missing in action in the heart of the Vietnam War. Having lost her father to cancer, Katia took up the mantle of caretaker, ensuring her mother and brothers were looked after. Her sense of duty extends to the boys at the group home, creating a web of obligations that stretches her emotional bandwidth thin. Amidst a power struggle at work with the board, Katia finds solace in the pages of romance novels and the soothing melodies of Nina Simone. When Seth Taylor, a familiar face from her high school days, reenters Katia's life, he brings with him a breeze of nostalgia and a reminder of a time when her dreams felt less tethered. As their friendship rekindles, Katia grapples with the idea of making choices for herself, even as the realization that she can no longer have children weighs heavily on her.